Breast sarcoma associated with tumor necrosis: a case report - Domínguez-Carrera, José Luis (2024)
Breast sarcoma (SM) is a rare cancer that affects the connective tissue of the breast. We present the case of a 47-year-old woman with a tumor in the right breast initially diagnosed as sarcoma by biopsy, but at the time of performing the mastectomy, the pathological analysis of the surgical specimen reported carcinoma, due to which the breasts were removed. axillary lymph nodes, which was later corrected to sarcoma by immunohistochemical studies. The patient underwent total mastectomy and axillary lymph node resection, followed by chemotherapy. Tumor necrosis, indicative of an aggressive tumor, complicated surgical management. The discordance in diagnosis underlines the importance of advanced techniques for accurate conclusion and timely treatment. Despite the size of the tumor and the aggressiveness of the sarcoma, the patient did not experience recurrence during post-treatment follow-up. This case highlights the need for effective communication between health professionals, the exhaustive review of pathological results and the multidisciplinary approach in the approach to breast sarcoma.